2021
DOI: 10.2147/clep.s294391
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Severe Covid-19 in Patients with Celiac Disease: A Population-Based Cohort Study

Abstract: Background Patients with celiac disease (CeD) are at increased risk of certain viral infections and of pneumococcal pneumonia, raising concerns that they may be susceptible to severe coronavirus disease 2019 (Covid-19). We aimed to quantify the association between CeD and severe outcomes related to Covid-19. Methods We performed a population-based cohort study, identifying individuals with CeD in Sweden, as defined by small intestinal villus atrophy diagnosed at all (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…[7][8][9] A recent population-based study of CD patients in Sweden found no increased risk of COVID-19-related outcomes among people with CD. 10 To our knowledge, this is the first study evaluating predictors of severe of COVID-19 outcomes among patients with CD. Strengths include its international nature and reliance on clinician reporting, likely enhancing the veracity of both CD and COVID-19 diagnoses.…”
Section: Discussionmentioning
confidence: 95%
“…[7][8][9] A recent population-based study of CD patients in Sweden found no increased risk of COVID-19-related outcomes among people with CD. 10 To our knowledge, this is the first study evaluating predictors of severe of COVID-19 outcomes among patients with CD. Strengths include its international nature and reliance on clinician reporting, likely enhancing the veracity of both CD and COVID-19 diagnoses.…”
Section: Discussionmentioning
confidence: 95%
“…However, the comorbidities identified as a significant predictor of morbidity and mortality on COVID-19 were more frequent in CD individuals than control ones [ 22 ]. A cohort study conducted in Sweden with 40,963 CD individuals showed that they were neither at increased risk of hospitalization for COVID-19 than the control ones nor at high risk for severe disease outcomes and mortality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CD interferes in the patient’s daily life beyond the gastrointestinal and health aspects of the disease such as their social, economic, and emotional status [ 11 ]. While several studies have been carried out on the pandemic’s psychological effects on the general public, patients, medical staff, children, and elderly [ 5 , 12 , 13 , 14 ], and several other studies were performed on celiac individuals during the pandemic [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], none evaluated the QoL of CD patients during the difficult times of the pandemic. Therefore, the objective of this research was to evaluate Brazilian celiac patients’ QoL during the pandemic caused by the outbreak, rapid spread, and subsequent restrictive measures caused by COVID-19, in addition to the dietary restrictions and other burdens caused by CD.…”
Section: Introductionmentioning
confidence: 99%
“…No significant alteration from general COVID-19 symptoms (Zingone et al, 2020;Gokden et al, 2020;Lebwohl et al, 2021) CHB, chronic hepatitis B; CHC, chronic hepatitis C; NAFLD, non-alcoholic fatty liver disease; HCC, hepatocellular carcinoma; IBD, irritable bowel disease; ACLF, acute-on-chronic liver failure; HIV, human immunodeficiency virus; TNF, tumor necrosis factor; GI, gastrointestinal.…”
Section: Cirrhosismentioning
confidence: 99%
“…In the current scenario, studies involving patient-response-based data collection and analysis have been done to determine the risk associated with CeD towards susceptibility and severity of COVID-19. A large CeD subset (n= 40,963) from nationwide histology-based population of patients with GI diseases in Sweden, ESPRESSO, was identified, and no significant increase in COVID-19-based hospitalizations, severity, or mortality was observed as compared to the control group (n= 183,892) ( Lebwohl et al., 2021 ). Another study from Italy, involving 171 CeD patients on gluten-free diet, also suggests no major association of CeD with increased risk of SARS-CoV2 infection or severity ( Zingone et al., 2020 ).…”
Section: Gi Diseasesmentioning
confidence: 99%